1. one number added to three times another number is 24. five times the first number added to

three times the other number is 36. find the numbers.

y = x + 4

3x - 2y = -7

We can substitute the first equation into the second

3x - 2(x + 4) = -7

3x - 2x - 8 = -7

x - 8 = -7

x = 1

y = 1 + 4

y = 5

So, the answer is (1, 5)

x=-7/2, y=1

Step-by-step explanation:

y=-2x-6

y=x+9

I'm going to use elimination.

2y=2x+9

y=-2x-6

3y=3

y=1

Enter y into one of the equations to find x.

2=2x+9

2x=-9+2

2x=-7

x=-7/2

A. The solution is (0.9,-0.7)

Solve for the first variable in one of the equations, then substitute the result into the other equation.

Point Form:

( 0.9 ,− 0.7 )

Equation Form:

x = 0.9 & y = − 0.7

(1,5)

Step-by-step explanation:

Use substitution, and plug the first equation into the 2nd one:

3x-2(x+4)=-7 -->

3x-2x-8 = -7 -->

x - 8 = -7

x = 1

Plug this into the first equation:

y = 1 + 4

y = 5

(1,5)

(-2,-4)

Step-by-step explanation:

2x-y=0

-2(x+3y=-14)

-2x-6y=28

x terms cancel

-y+-12y=-13y

0+28=28

-7y=28

28/-7

y=-4

plug into the orginal equation

2x-(-4)=0

simply: 2x+4=0

elimante the 4

2x=-4

divide by 2

x=-2

A. The unique solution to the system is

Step-by-step explanation:

You can follow these steps to solve the system of equation by the Elimination Method:

- Multiply the first equation by -0.7, then add both equations and solve for "y":

- Substitute the value of "y" into any original equation to find the value of "x". Then:

Therefore, the unique solution to the system is

A. The unique solution to the system is

Step-by-step explanation:

You can follow these steps to solve the system of equation by the Elimination Method:

- Multiply the first equation by 0.5, then add both equations and solve for "y":

- Substitute the value of "y" into any original equation to find the value of "x". Then:

Therefore, the unique solution to the system is

Step-by-step explanation:

x + 3y = 24multiply by -1

5x + 3y = 36

-x - 3y = -24 (result of multiplying by -1)

5x + 3y = 36

add

4x = 12

x = 12/4

x = 3 <

x + 3y = 24

3 + 3y = 24

3y = 24 - 3

3y = 21

y = 21/3

y = 7 <

Step-by-step explanation:

x + 3y = 24multiply by -1

5x + 3y = 36

-x - 3y = -24 (result of multiplying by -1)

5x + 3y = 36

add

4x = 12

x = 12/4

x = 3 <

x + 3y = 24

3 + 3y = 24

3y = 24 - 3

3y = 21

y = 21/3

y = 7 <

2/4 is the answerstep-by-step explanation: x= total pieces both ate 9 pieces mindy ate 3 so troy ate 6 6= (1/4)x x =24...Read More

2 more answers

Step-by-step explanation:Let S be the number of cans that Shane had collected.Abha had collected 178 more cans than Shane did, then Abha had collected S+178 cans. Shane and Abha e...Read More

3 more answers

(a) The confidence interval is: 0.0304 ≤ π ≤ 0.0830.(b) Upper confidence bound = 0.0787Step-by-step explanation:(a) The confidence interval for p (proportion) can be calculated asN...Read More

3 more answers

answerim : nstep-by-step explanation: im not sure but my dad knows...Read More

2 more answers

the answer would be 484step-by-step explanation: just multiply 0.484 times 1,000 (formula)...Read More

2 more answers

i know the answer is 3step-by-step explanation:...Read More

2 more answers

- What is the output value for the following function if the input value...
- Rewrite 4 5 × 20 as a single fraction...
- Gabriel used 1/3 of a liter of milk to make 1/9 of a jug of tea. how m...
- How can i find answer to this problem?...
- Monica purchased adult and youth tickets for the fair. she bought x ad...
- The percent decrease in the price of bottled water...
- Idon't know how to figure the answer. give a answer soon as possible...
- Find the product of 5/12 and 3/8. express your answer in simplest form...
- If prices increase at a monthly rate of 3.53.5%, by what percentage d...
- Use a coterminal angle to find the exact value of the expression. do n...